Genomic-Assisted Marker Development Suitable for CsCvy-1 Selection in Cucumber Breeding - Kahveci, Erdem; Devran, Zübeyir; Özkaynak, Ercan; Hong, Yiguo; Studholme, David J.; Tör, Mahmut (Frontiers in Plant Science, 2021)
Cucumber is a widely grown vegetable crop plant and a host to many different plant pathogens. Cucumber vein yellowing virus (CVYV) causes economic losses on cucumber crops in Mediterranean countries as well as in some part of India such as West Bengal and in African countries such as Sudan. CVYV is an RNA potyvirus transmitted mechanically as well as by whitefly (Bemisia tabaci) in a semipersistent manner. Control of this virus is heavily dependent on the management of the insect vector and breeding virus resistant lines. DNA markers have been used widely in conventional plant breeding programmes via marker-assisted selection (MAS). However, very few resistance sources against CVYV in cucumber exist and also the lack of tightly-linked molecular markers to these sources restricts the rapid generation of resistant lines. In this work, we used genomics coupled with bulked segregant analysis method and generated MAS-friendly KASP (Kompetitive Allele Specific PCR) markers suitable for CsCvy-1 selection in cucumber breeding using a segregating F2 mapping population and commercial plant lines. Variant analysis was performed to generate SNP-based markers for mapping the population and genotyping the commercial lines. We fine-mapped the region by generating new markers down to 101 kb with eight genes. We provide SNP data for this interval, which could be useful for breeding programmes as well as cloning the candidate genes.